An overview of water electrolysis technologies for green hydrogen production. (November 2022) - Shiva Kumar, S.; Lim, Hankwon
Abstract: Decarbonizing the planet is one of the major goals that countries around the world have set for 2050 to mitigate the effects of climate change. To achieve these goals, green hydrogen that can be produced from the electrolysis of water is an important key solution to tackle global decarbonization. Consequently, in recent years there is an increase in interest towards green hydrogen production through the electrolysis process for large-scale implementation of renewable energy-based power plants and other industrial, and transportation applications. The main objective of this study was to provide a comprehensive review of various green hydrogen production technologies especially on water electrolysis. In this review, various water electrolysis technologies and their techno-commercial prospects including hydrogen production cost, along with recent developments in electrode materials, and their challenges were summarized. Further some of the most successful results also were described. Moreover this review aims to identify the gaps in water electrolysis research and development towards the techno-commercial perspective. In addition, some of the commercial electrolyzer performances and their limitations also were described along with possible solutions for cost-effective hydrogen production Finally, we outlined our ideas, and possible solutions for driving cost-effective green hydrogen production for commercial applications. This information will provide future research directions and a road map for the development/implementation of commercially viable green hydrogen projects. Highlights: Water electrolysis is one of the most promising methods for green hydrogen generation. Green hydrogen provides a sustainable solution for future energy demands and decarburization. This review summarizes various water electrolysis technologies for techno-commercial perspective and their challenges. Finally, we outlined our ideas/recommendations for future research and developments.